2013
DOI: 10.1063/1.4794127
|View full text |Cite
|
Sign up to set email alerts
|

Thermal equation of state and thermodynamic properties of molybdenum at high pressures

Abstract: A comprehensive P-V-T dataset for bcc-Mo was obtained at pressures up to 31 GPa and temperatures from 300 to 1673 K using MgO and Au pressure calibrants. The thermodynamic analysis of these data was performed using high-temperature Birch-Murnaghan (HTBM) equations of state (EOS), Mie-Grüneisen-Debye (MGD) relation combined with the room-temperature Vinet EOS, and newly proposed Kunc-Einstein (KE) approach. The analysis of room-temperature compression data with the Vinet EOS yields V0 = 31.14 ± 0.02 Å3, KT = 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 60 publications
6
48
1
Order By: Relevance
“…It's found that (Litasov, 2013)the values of γ derived from the model Mo-1 seem too high, whereas the model Mo-2 yielded consistent results with shock-wave (SW) data (Asimow, 2009) and theoretical calculations (Zeng, 2011).…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…It's found that (Litasov, 2013)the values of γ derived from the model Mo-1 seem too high, whereas the model Mo-2 yielded consistent results with shock-wave (SW) data (Asimow, 2009) and theoretical calculations (Zeng, 2011).…”
Section: Introductionmentioning
confidence: 70%
“…Litasov et al (Litasov, 2013) had discussed two other forms of γ for Mo. One is from Mie−Gruneisen−Debye (MGD) EOS, γ has the following form…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whenever we process or make comparisons to experimental data in the solid phase, we employ the above expressions with a reference density of ̺ 0 = 10.228 g/cm 3 at T 0 = 298 K. 73 At the melting point (2900 K) 74 the density has reduced by about 7%.…”
Section: Summary and Discussionmentioning
confidence: 99%